Kohitang Mountaindrygastropod Lmollusks’ Ecological Grouping - Xasanovna, Jo‘rayeva Samiya; Karimovna, Abdulazizova Shoira (European Journal of Life Safety and Stability (2660-9630), 2021)
The ecological grouping and characteristics of terrestrial crustacean mollusks in connection to moisture on the eastern slopes of Mount Kohitang, which is regarded to be the southwestern section of the Pamir-Alay mountain chain, are described in this article.